Effective removal of Pb(II) by low-cost fibrous silica KCC-1 synthesized from silica-rich rice husk ash - Rosalyza, Hasan; Chi, Cheng Chong; S. N., Bukhari; Rohayu, Jusoh; Setiabudi, H. D. (Elsevier, 2019)
Rice husk ash was utilized as a low-cost silica precursor in preparing KCC-1(RHA) for Pb(II) removal. The characterization results revealed the comparable properties of KCC-1(RHA) with the conventional KCC-1. The optimum adsorption conditions were achieved at initial concentration of 322.06 mg/L, adsorbent dosage of 2.4 g/L, and time of 117 min, with Pb(II) removal of 75%. The experimental results followed the pseudo-second-order kinetic model (R2 ≥ 0.9950) and Langmuir isotherm model (R2 = 0.9934). The KCC-1(RHA) showed good performance during five cycles of adsorption-desorption, thus, affirmed great potential of RHA as silica precursor in synthesizing KCC-1(RHA) for excellent Pb(II) removal.